2018
DOI: 10.1097/wco.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography as a means to characterize visual pathway involvement in multiple sclerosis

Abstract: OCT provides insights into multiple sclerosis beyond the visual pathway. It is capable of quantifying the major pathological hallmarks of the disease, specifically inflammation and neuroaxonal degeneration. OCT, therefore, has the potential to become another mainstay in the monitoring of multiple sclerosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…While thinning of the peripapillary retinal nerve fiber layer (pRNFL), containing unmyelinated axons, and the ganglion cell layer, containing their cell bodies, reflect neuroaxonal atrophy as a consequence of retrograde neurodegeneration, the inner nuclear layer (INL) is associated with inflammation manifesting in thickening and edema (31,(34)(35)(36)(37)(38)(39)(40). The ganglion cell layer is usually-due to similar contrast on OCT images-analyzed in combination with the inner plexiform layer (GCIP).…”
Section: Introductionmentioning
confidence: 99%
“…While thinning of the peripapillary retinal nerve fiber layer (pRNFL), containing unmyelinated axons, and the ganglion cell layer, containing their cell bodies, reflect neuroaxonal atrophy as a consequence of retrograde neurodegeneration, the inner nuclear layer (INL) is associated with inflammation manifesting in thickening and edema (31,(34)(35)(36)(37)(38)(39)(40). The ganglion cell layer is usually-due to similar contrast on OCT images-analyzed in combination with the inner plexiform layer (GCIP).…”
Section: Introductionmentioning
confidence: 99%
“…All these characteristics have meant that OCT has revolutionized daily clinical practice in neuro-ophthalmology, because the technique makes it possible to quantify, non-invasively, rapidly, objectively, reliably, and highly reproducibly [12], the major pathological hallmarks of the disease, specifically, inflammation and neuroaxonal degeneration [13]. It also uses the same anatomical area in the follow-up examinations of the eye, which makes it possible to monitor neurological deterioration in neurodegenerative pathologies, thereby serving as a reliable progression biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are indicating decreased ppRNFL thickness in MS patients with or without ON 3,5,6 . Previous studies reported decreased ppRNFL thickness might be associated with optic radiation damage in eyes without ON 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that OCT is an essential imaging method for monitoring neurodegenerative diseases and MS. It was found that peripapillary retinal nerve fiber layer (ppRNFL) and macular thickness were associated with disease severity, cognitive and physical dysfunction in patients with MS [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%